“E aí, pesquisador, comunicar pra quê?": o podcast como estratégia e mídia para a divulgação da ciência - Borges, Diogo Oliveira (2020)
Disseminating science outside the scientific community, bringing language closer, traditionally inaccessible to the majority of the population, and creating a channel of dialogue with society, has been a necessary work, sought by researchers to break with conventional practices, usually based on meeting government or business interests as a one-way speech. In this support, the present work aims to understand how the dissemination of science can join the podcast, audio media distributed on digital streaming platforms or digital social networks, for its realization. In this way, it seeks to answer the problem: "How to disseminate science in contemporary times through the podcast?". The research resulted in the creation of a podcast channel - “Communicate for what?” - which, carried out in the form of a round table with several researchers and professionals, both from the studies of Science Communication and radio -, sought to raise possible strategies and formats for the communication of science by podcast from the media itself. It is a series of podcasts focused on the main focuses and obstacles to the dissemination of science as a facilitating guide, so that this resource can be more widely disseminated and used by researchers to disseminate their own work. The research provides subsidies to rethink communication strategies for science and reflects on the potential of the podcast in the Brazilian sound scene, in view of the reach of this media.